CYTOLOGICAL, HPV GENOME, AND HISTOPATHOLOGICAL CORRELATION OF CERVICAL SMEARS IN FEMALES 30 YEARS AND ABOVE - SINGAL, POONAM; KUMAR, NINDER; KUNDAL, DEEPAM; SINGH, KARANBIR; KUMAR, RAMESH; KAUR, MANPREET (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to evaluate the patterns of cervical smear cytology in relation to human papillomavirus (HPV) and to correlate with histopathological diagnosis in females of 30 years and above. Methods: The 2-year prospective study was done in the Department of Pathology in 100 patients who attended the Gynaecology OPD of Govt. Medical College, Patiala. The cervical brushings obtained were subjected to cytological examination by liquid-based cytology through SurePath method and for HPV evaluation by BD Onclarity HPV assay. The cytological findings were further correlated with histopathological examination. Results: Majority of the females were in the age group of 30−45 years (62%). There was high incidence of dysplasia and malignancy in those who were of parity 3, 4, and above. The most common presenting symptom was discharge per vaginum (DPV) seen in 28% of cases. Maximum cases on cytology were diagnosed as NILM (including inflammatory pathology, 49%) followed by LSIL as 14% and malignant as 13%. Overall HPV genome was detected in 54% of the samples, the cases diagnosed as dysplasia and malignancy showed 68.42% and 100% presence of HPV, respectively. This was found to be statistically significant (p<0.05). Conclusion: Pap smear along with HPV evaluation is an effective screening method for the detection of pre-invasive lesions and cancers of cervix that are potentially curable.